Pengembangan Bahan Ajar Digital Berbasis Discovery Learning dengan Augmented Reality Untuk Meningkatkan Kemampuan Berfikir Kritis Siswa Pada Pembelajaran IPA di Sekolah Dasar - Sri Sutanto Sutanto; Irwan Koto; Endang Widi Winarni (Jurnal Kajian Pendidikan Dasar (Kapedas), 2022)
The purpose of this study is to develop, describe the level of feasibility, determine user responses and determine the effectiveness of digital teaching materials based on discovery learning with augmented reality to improve students' critical thinking skills. The type of research used is research and development. The research model in the development of teaching materials is the ADDIE model. The types of data used are quantitative and qualitative data using instruments in the form of interviews, needs analysis questionnaires, questions, expert validation sheets and user response questionnaires. Based on the results of the study, it can be concluded that the teaching materials developed are suitable for use as teaching materials in the Natural Sciences (IPA) class V material for animal and human movement organs. Aspects that are validated include the feasibility of the material, language, and design. The percentage of material expert validation results is 71%. From the validation of linguists 83% and the validation of design experts 90%. The user's response is very good because the results of the questionnaire analysis of class V students' responses from students, aspects of continuity of content are 83%, aspects of design are 83% and aspects of material interest are 80%. The teaching materials developed are effective in improving the critical thinking skills of fifth grade students at SDN 107 Bengkulu Utara. This is based on the results of the effect size test of 93.33%.